Language learning with physical activity: The case of learning Italian in tourism - Mojca Kompara Lukančič (Peoples' Friendship University of Russia (RUDN University), 2021)
The aim of the paper is to present how movement improves language learning in the case of rehearsing regular and irregular Italian verbs. In the paper we address the importance of language learning in the frame of Language for Special Purposes (LSP), providing an overview of it and continuing to the frame of Language for Tourism (LfT) and Content and Language Integrated Learning (CLIL) in relation to movement and physical activity where examples of good practice are presented. As seen from the examples of good practice, the introduction of movement into the school curricula in connection to language learning stops too soon in elementary school and does not continue onwards. The survey is composed of an experiment where students from the University of Maribor rehearse regular and irregular Italian verbs performing a physical activity and a control group of students rehearsing the verbs without the introduction of physical activity, language testing and a questionnaire. The main objective of the paper is to show through the experiment, the language testing and the questionnaire that movement improves understanding and memorising Italian verbs and, consequently, language learning. As it is seen from the results of the language testing, we can conclude that the experimental groups achieved better results in conjugating the verbs, both regular and irregular, and were also more successful in providing correct forms of the regular and irregular verbs compared to the control group. From the questionnaire it is visible that movement improves language learning and memorising verbs. The respondents answered that movement improved topic focus (97%) and should be introduced also in subjects other than languages (57%).